Acute effects of whole body vibration and weighted vest on muscle strength and balance in elderly - Srisaphonphusitti, Lertwanlop; Manimmanakorn, Nuttaset N.; Manimmanakorn, Apiwan; Panyaek, Nichanun; Hamlin, Michael J. (Asia-Pacific Journal of Science and Technology, 2021)
This study aimed to investigate the physiological consequence of an acute bout of whole body vibration (WBV) combined with wearing a weighted vest (WBV+WV) compared to WBV or WV alone. Fifty-two elderly volunteers (65.2 ± 3.7 years, mean ± standard deviation (SD)) were randomly allocated into 3 groups: WBV (n= 17, 10 sets of 1 minutes squat exercises interspersed with 60 s rest on a vibration platform with a frequency of 30 Hz and amplitude 2 mm), WV (n= 16, the same squat exercises with an additional 10% of bodyweight loaded into a weighted vest) and WBV+WV (n= 19, combination of both regimes). Heart rate was monitored at baseline, during and 15 minutes post-exercise, while muscle strength, balance, and functional mobility were measured before and 15 minutes post-exercise. Heart rate increased significantly with acute exercise but was not different between groups throughout the experiment. Compared to pre-exercise, WBV improved muscle strength (11% ± 5.6%, mean ± 95% CI, p-Value < 0.01), single leg stance test (43.5% ± 22.1%, p-Value < 0.01), and timed up and go test (5.3% ± 2.7%, p-Value < 0.01) 15 minutes post-exercise, while the WV exercise showed improvement only in timed up and go test (3.9% ± 1.3%, p-Value < 0.01). Compared to pre-exercise, combining WBV+WV increased single leg stance test (40.8% ± 37.7%, p-Value = 0.01) and timed up and go test (3.9% ±1.3%, p-Value < 0.01) post-exercise. Since WBV had an acute improvement on all outcomes, it may be useful as a warm-up activity for older adults.